Expert System for Sars Cov-2 Disease with Comorbidities Using a Combination of Case Based Reasoning and Certainty Factor Methods - Adinda, Sity Tree; Samsudin, Samsudin; Irawan, Muhammad Dedi (Jurnal Penelitian Medan Agama, 2024)
Virus Sereve Acute Respirator Syndrome Corona Virus 2 (SARS COV-2) is a virus that is also caused by a corona virus which if exposed to this virus will cause a serious infection that has the potential to be life threatening. In various cases, it turns out that infection with the SARS COV-2 virus can have effects on several organs such as the lungs, heart, blood vessels, kidneys and liver. In this regard, some people think that the SARS COV-2 virus is a scary virus that makes people afraid to come to health services so that it has an impact on uncontrolled blood sugar and is prone to complications. To overcome the increase in mortality due to the SARS COV-2 virus with comorbidities with the help of artificial intelligence to build a knowledge-based system in the medical field for diagnosing SARS COV-2 with comorbidities using a combination of Case Based Reasoning and Certainty Factor methods. The Case Based Reasoning method is used as a rule to detect disease symptoms by diagnosing new cases based on old cases. While the Certainty Factor is used to increase the value of confidence and feasibility. The percentage of confidence value given by experts in order to get maximum results.